Surface evaluations of a nanocomposite after different finishing and polishing systems for anterior and posterior restorations. Issue 12 (9th June 2021) - Monterubbianesi, Riccardo; Tosco, Vincenzo; Orilisi, Giulia; Grandini, Simone; Orsini, Giovanna; Putignano, Angelo
Abstract: This study aims to evaluate the effects of different finishing and polishing (F/P) systems on gloss and surface morphology of a new nanocomposite. Thirty discs of Filtek Universal Restorative material (3 M, ESPE) were prepared and divided into six groups ( n  = 5). Group A and B followed F/P protocols for anterior restorations, whereas Group C and D for posterior ones. Group E represented the control (covered by Mylar strip) and Group F represented the nanocomposite placement by means of clinical hand instruments; Groups E and F did not undergo F/P procedures. Among the polished groups, Group B showed the highest values (68.54 ± 7.54 GU), followed by Group A and D (46.87 ± 5.52 GU; 53.76 ± 2.65 GU). Finally, Group C (37.38 ± 4.93 GU) displayed the lowest results. Overall, Group E showed the highest gloss values (93.45 ± 8.27 GU), while Group F presented the lowest ones (1.74 ± 0.64 GU). Surface analysis revealed that Group A, C, and D displayed a smooth surface. Group B showed the lowest irregularities. Group E exhibited the most uniform superficial morphology. On the other hand, Group F displayed the most irregular one. In conclusion, using the tested material, only two protocols achieved appropriate gloss values. Then, clinicians might use the protocols of Group B and Group D, for anterior and posterior restorations, respectively. Abstract : The clinician should avoid unpolished surface in resin‐based composite restorations. In finishing and polishing procedures rigid instruments can be used on anterior restorations instead than in posterior ones. On the other hand, for posterior restorations, flexible instruments, which perfectly adapt to the complex occlusal anatomy, should be used.